The Mediterranean Lifestyle: The Power of Food - Charissa Lim; Alexa Hosey; Farah Tadros; Madison Woodard; Jeanette Andrade (EDIS)
The Mediterranean diet dates back to the early 1960s, in which the population living among the Mediterranean basin, much of Greece and Southern Italy consumed high amounts of fruits, vegetables, nuts, legumes, and unprocessed cereals with minimal consumption of meat. This dietary pattern has been shown to improve heart health, maintain weight, and reduce the risk for chronic diseases such as cardiovascular disease and type 2 diabetes. This new 6-page publication discusses the Mediterranean dietary pattern and provides tips to incorporate this lifestyle into daily life, as well as sample recipes. Written by Charissa Lim, Alexa Hosey, Farah Tadros, Madison Woodard, and Jeanette Andrade, and published by the UF/IFAS Food Science and Human Nutrition Department. https://edis.ifas.ufl.edu/fs399